2021
DOI: 10.21203/rs.3.rs-525866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors that Influence Satisfaction of People Living with HIV(PLHIV) with Differentiated ART Delivery Models in East Central Uganda: A Cross-Sectional Study

Abstract: Background The World Health Organization and Uganda Ministry of Health recommend differentiated service delivery models (DSDM) as patient-focussed approaches for delivering antiretroviral therapy for people living with HIV/AIDS (PLHIV) who have undetectable viral loads. We sought to determine the factors significantly associated with patient satisfaction with ART services amongst PLHIV enrolled in DSDMs. Methods This was a cross-sectional study of a random sample of PLHIVs accessing ART within DSDMs at nine … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…9 A study in East and Central Uganda found that more PLHIV enrolled in CDDP than in other differentiated service delivery models. 10 During the COVID-19 lockdown, ART delivery was best done by community-based ART delivery models due to patients' demand. 11 Currently, ART coverage in Uganda is currently at 83%, and some facilities are overcrowded with PLHIV seeking ART services.…”
Section: Introductionmentioning
confidence: 99%
“…9 A study in East and Central Uganda found that more PLHIV enrolled in CDDP than in other differentiated service delivery models. 10 During the COVID-19 lockdown, ART delivery was best done by community-based ART delivery models due to patients' demand. 11 Currently, ART coverage in Uganda is currently at 83%, and some facilities are overcrowded with PLHIV seeking ART services.…”
Section: Introductionmentioning
confidence: 99%